Percutaneous mechanical circulatory support and survival in patients resuscitated from Out of Hospital cardiac arrest: A study from the CARES surveillance group. (January 2021) - Tram, Julie; Pressman, Andrew; Chen, Nai-Wei; Berger, David A.; Miller, Joseph; Welch, Robert D.; Reynolds, Joshua C.; Pribble, James; Hanson, Ivan; Swor, Robert
Abstract: Introduction: Maintenance of cardiac function is required for successful outcome after out-of-hospital cardiac arrest (OHCA). Cardiac function can be augmented using a mechanical circulatory support (MCS) device, most commonly an intra-aortic balloon pump (IABP) or Impella®. Objective: Our objective is to assess whether the use of a MCS is associated with improved survival in patients resuscitated from OHCA in Michigan. Methods: We matched cardiac arrest cases during 2014–2017 from the Cardiac Arrest Registry to Enhance Survival (CARES) in Michigan and the Michigan Inpatient Database (MIDB) using probabilistic linkage. Multilevel logistic regression tested the association between MCS and the primary outcome of survival to hospital discharge. Results: A total of 3790 CARES cases were matched with the MIDB and 1131 (29.8%) survived to hospital discharge. A small number were treated with MCS, an IABP (n = 183) or Impella® (n = 50). IABP use was associated with an improved outcome (unadjusted OR = 2.16, 95%CI [1.59, 2.93]), while use of Impella® approached significance (OR = 1.72, 95% CI [0.96, 3.06]). Use of MCS was associated with improved outcome (unadjusted OR = 2.07, 95% CI [1.55, 2.77]). In a multivariable model, MCS use was no longer independently associated with improved outcome (ORadj = 0.95, 95% CI [0.69, 1.31]). In the subset of subjects with cardiogenic shock (N = 725), MCS was associated with improved survival in univariate (unadjusted OR = 1.84, 95% CI [1.24, 2.73]) but not multi-variable modeling (ORadj = 1.14, 95% CI [0.74, 1.77]). Conclusion: Use of MCS was infrequent in patients resuscitated from OHCA and was not independently associated with improvement in post arrest survival after adjusting for covariates.